2018
DOI: 10.1186/s13071-018-3088-x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the infectivity and pathogenicity of Cryptosporidium avium provides new information on parasitic sites within the host

Abstract: BackgroundCryptosporidium spp. are protozoans that cause diarrheal illness in humans and animals, including birds, worldwide. The present study was aimed to revisit the infectivity and pathogenicity of C. avium, recently considered to be a valid avian-infecting species of Cryptosporidium, and foster further understanding of its biological characteristics.ResultsResults showed that no Cryptosporidium oocysts were detected in the feces of experimentally inoculated BALB/c mice, Mongolian gerbils, quail or budgeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
2
11
1
Order By: Relevance
“…This result should be attributed to the immunodeficient situation that flared up the infection. This was evident research [46], and another study [47] found a higher number of developmental stages in the epithelial cells of the infected control group's gut [47,48]. A reduction in the villus to crypt ratio in mice infected with C. parvum oocysts was observed by some studies.…”
Section: Discussionmentioning
confidence: 68%
“…This result should be attributed to the immunodeficient situation that flared up the infection. This was evident research [46], and another study [47] found a higher number of developmental stages in the epithelial cells of the infected control group's gut [47,48]. A reduction in the villus to crypt ratio in mice infected with C. parvum oocysts was observed by some studies.…”
Section: Discussionmentioning
confidence: 68%
“…No pathology. Abe and Matsubara, 2015 C. avium Buderigar, Cockatiel P Melopsittacus undlates Nymphicus hollandicus China KM267556 none none unknown Zhang et al (2015) C. avium * Red-crowned parakeet, Chicken, Budgerigar P Cyanoramphus novaezealandiae, Gallus gallus , Melopsittacus undlates Czechia KU058875-78 KU058879-82 KU058883-86 none Holubová et al (2016) C. avium Canary P Serinus canaria Brazil MG832882 none none none Camargo et al (2018) C. avium * Cockatiel P , Chicken* Nymphicus hollandicus , Gallus gallus China JQ246415 JQ320301 JQ798893 none Cui et al (2018) C. avium * Mallard, Chicken, Pheasant W,A Anas platryrhynchos , Gallus gallus , Phasianus colchicus Czechia none none none none Holubová et al (2018) C. avium Red-crowned parakeet, Budgerigar P Cyanoramphus novaezealandiae, ...…”
Section: Resultsmentioning
confidence: 99%
“…C. avium was confirmed by PCR from a Major Mitchell's cockatoo in the USA, which, like the iguanas and ostriches, presented with cloacal prolapse, but also renal cryptosporidiosis ( Curtiss et al, 2015 ). Cui et al (2018) suggested that the bursa of Fabricius was the main site of infection for C. avium , which was established via experimental infection of chickens – which showed no clinical signs during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Subtype IIdA19G1 oocysts of C. parvum were used in this study. Oocysts were purified and counted according to a previous study [ 24 ] and stored in phosphate buffer solution (PBS) at 4 °C. N-lauroylsarcosine sodium salt (LSS) was used in the crude DNA extraction, and a homemade DNA banding column was used to purify DNA from the crude extracts (Additional file 1 : Figure S1).…”
Section: Methodsmentioning
confidence: 99%